2015
DOI: 10.1007/s00520-015-2676-y
|View full text |Cite
|
Sign up to set email alerts
|

Variations in intensity of end-of-life cancer therapy by cancer type at a Canadian tertiary cancer centre between 2003 and 2010

Abstract: BackgroundAggressive medical management of cancer patients at the end of life (EOL) is an indicator of health services quality. We evaluated the variations in EOL cancer therapy utilization and in acute care hospital deaths across different types of cancer within the setting of a regionalized cancer program.MethodsIntravenous chemotherapy and radiotherapy use within the last 14 and 30 days of life was identified through the Alberta Cancer Registry and then verified by chart review for cancer decedents residing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 23 publications
3
28
0
Order By: Relevance
“…Approximately half of the patients died in an acute hospital setting. While the sample selections differed, a study in Canada reported 34% of cancer patients dying in the hospital (21). A study of US Medicare beneficiaries age 65 or older reported a reduction in the proportion of cancer patients dying in an acute care hospital from 30% in 2000 to 22% in 2009 (22).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately half of the patients died in an acute hospital setting. While the sample selections differed, a study in Canada reported 34% of cancer patients dying in the hospital (21). A study of US Medicare beneficiaries age 65 or older reported a reduction in the proportion of cancer patients dying in an acute care hospital from 30% in 2000 to 22% in 2009 (22).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined factors associated with RT use in the end of life for patients with rectal cancer. [18][19][20][21][22][23] However, most of these studies evaluated these associations using cohorts consisting of several malignancies including colorectal, lung, breast, and prostate, thus limiting knowledge about cancer-specific trends. This is an important limitation in the current literature since the clinical management of cancer is heterogeneous across disease sites.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have attempted to elucidate factors and trends associated with RT use during the end of life, they have been mostly limited to the Medicare population, thus limiting generalizability to younger populations. [18][19][20][21][22][23] In addition, these studies have not examined RT use during the end of life specifically for patients with rectal cancer. Given the particular clinical management and natural history of a rectal tumor, factors associated with RT use as well as its prevalence in the end-of-life setting may differ for patients with rectal cancer compared to other malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with HNSCC undergo computed tomography (CT) prior to treatment to determine staging and treatment target volumes as well as for posttreatment surveillance purposes. Use of readily available radiation treatment planning software effectively and reliably measures body tissue volumes . Availability of these imaging series collected in a standard treatment and surveillance protocol provides the opportunity to evaluate the three‐dimensional pre‐ and posttreatment tissue volumes in these populations.…”
Section: Introductionmentioning
confidence: 99%
“…Use of readily available radiation treatment planning software effectively and reliably measures body tissue volumes. 15 Availability of these imaging series collected in a standard treatment and surveillance protocol provides the opportunity to evaluate the three-dimensional pre-and posttreatment tissue volumes in these populations. This retrospective study determined the degree of pharyngeal structure volumetric changes among patients undergoing radical curative CRT for HNSCC.…”
Section: Introductionmentioning
confidence: 99%